2011
DOI: 10.1002/macp.201000634
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Vapor‐Phase Polymerization of PEDOT and a Siloxane into Organic/Inorganic Hybrid Thin Films

Abstract: The co‐vaporization and simultaneous polymerization of EDOT and APTES on a FTS‐coated substrate resulting in a homogeneous PEDOT/ASSQ thin film is described. The physicochemical properties of the film, including surface hardness, solvent mechanical wear resistance, and resistance to scratch, were much better than those of pure PEDOT. A PEDOT/ASSQ hybrid film with homogeneous morphology resulted, as judged by AFM topography scans, surface roughness calculations, and SEM images. The ASSQ proportion in the hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
0
6
0
3
Order By: Relevance
“…18,19 최근에는 본 연구진은 기 상중합을 이용한 유-무기 하이브리드 소재를 연구하여 오고 있다. [20][21][22][23][24][25][26] (Figure 1(a)). GO 수용액에 천연 고분자인 SCC를 1 wt% 첨가하여 동결주조하자 균일한 표면을 가지는 구형입 자를 만들 수 있었다 (Figure 1(b (Figure 3(c), (f), (i)).…”
Section: 폴리머 제42권 제3호 2018년unclassified
“…18,19 최근에는 본 연구진은 기 상중합을 이용한 유-무기 하이브리드 소재를 연구하여 오고 있다. [20][21][22][23][24][25][26] (Figure 1(a)). GO 수용액에 천연 고분자인 SCC를 1 wt% 첨가하여 동결주조하자 균일한 표면을 가지는 구형입 자를 만들 수 있었다 (Figure 1(b (Figure 3(c), (f), (i)).…”
Section: 폴리머 제42권 제3호 2018년unclassified
“…Choi et al 12 reported that silane precursors (bridged T type) including a 3,4-ethylenedioxythiophene (EDOT) moiety can improve the physicochemical properties of PEDOT based organic-inorganic hybrid films. Han et al 13 reported that a PEDOT/ASSQ organic-inorganic hybrid film fabricated by co-vaporization of EDOT and a silane precursor afforded increased physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The other technique is VPP which is an emerging technique that has the ability to overcome issues associated with polymer insolubility, as in‐situ polymerization occurs on the substrate. Issues involving the simultaneous synthesis of more than one polymer have been addressed by modifying the VPP process . Recent work by our group has also demonstrated the successful deposition of multiple electro‐active layers by sequentially introducing different monomer vapors into the polymerization process.…”
Section: Introductionmentioning
confidence: 99%